Faktor- faktor yang Mempengaruhi Penerapan Standar Akuntansi Keuangan Entitas Mikro Kecil dan Menengah dalam Penyusunan Laporan Keuangan pada UMKM Ritel - Nurhasan, Nurhasan; Nurali, Nurali; Septian, Dimas Dwi (Universitas Batanghari, 2025)
This research was conducted in Cileungsi, Bogor Regency, from a financial perspective that encourages economic growth in villages. This can be realized by implementing the financial accounting standards for micro, small, and medium entities (SAK EMKM). The research aims to determine the factors influencing the implementation of SAK EMKM, identify factors that hinder the implementation of SAK EMKM, and provide practical suggestions to improve MSME compliance with standard bookkeeping. This research uses a mixed quantitative and qualitative method approach using surveys and interviews. The results of the data using SPSS obtained the calculated t value of the HR Competence and Business Size variables greater than the t table 1.703 so that for the two independent variables Ha is accepted and H0 is rejected and the multiple linear regression equation is obtained as follows: Y = 7.788 + 0.290 + 0.484 The constant of 7.788 means that if the Business Size and HR Competence are 0, then the Implementation of MKM SAK is 7.788, the regression coefficient of Business Size is 0.484 so if the other independent variables remain and the business size increases by 1 then the Implementation of EMKM SAK will increase by 0.484. The coefficient is positive meaning there is a positive relationship between12 Business Size and the Implementation of EMKM SAK. The regression coefficient of HR Competence is 0.290 so if the other independent variables remain and the business size increases by 1 then the Implementation of EMKM SAK will increase by 0.290. A positive coefficient means that there is a positive relationship between HR Competence and the Implementation of EMKM SAK. The researcher draws the following conclusions from the data analysis and discussion of the study findings described above as follows: 1. Business size has a partial and significant effect on the implementation of EMKM SAK in the preparation of financial reports in Retail MSMEs. 2. HR Competence has a partial and significant effect on the implementation of EMKM SAK in the preparation of financial reports in Retail MSMEs. 3. Business Size and HR Competence have a simultaneous effect on the implementation of EMKM SAK in the preparation of financial reports in Retail MSMEs.